La educación en tiempos de bicentenario - Gonzáles Sarmiento, Olga (2011)
The educational situation in Latin America has lead to consider educational goals to guide education development to 20 21 . They seek to increase quality in education considering student training at schools, teacher's presence, research, social participation, in general a continuous education development.